Examination of the Effect of Chemical Composition on Laser Polished Cast Irons with Spheroidal Graphite - O. Özaydin; L. Kreinest; J. Schüssler; E. Willenborg; A. Bührig-Polaczek (Archives of Foundry Engineering)
Spherical Graphite Cast Iron (SGI) alloys have been used as a material in mold making for deep-drawing dies and glass molds due to their excellent machinability and thermal conductivity. Moreover, other advantages of SGI alloys are their supreme castability, to cast complex geometries in comparison to steel, and the use of up to 90 % recycled materials, especially steel scrap. This leads to a significant reduction of material and energy usage, thereby contributing to both financial savings and ecological benefits. Nevertheless, the mold application of SGI alloys is restricted by inherent limitations, including low hardness values and high surface roughness after machining and even after manual polishing. To overcome these drawbacks a laser polishing process can be beneficial to obtain a graphite-free and steel-like hard surface and to enable a very low surface roughness, optionally in combination with a final manual polishing step. According to the state of the art, the graphite in the SGI structure could not yet be entirely removed from the surface layer by laser polishing, which on one hand leads to a higher roughness and on the other hand raises the risk of cracks. In the current investigations, the SGI alloys with different chemical compositions were cast in three different geometries, machined and subsequently laser polished. After laser polishing, remelting depth and the tendency for surface cracks were investigated. In addition, the influence of graphite morphology on the laser polishing process was examined for these three alloys and three different geometries (wall thicknesses), which all have influences on the microstructure formation. This led to laser polishing parameters to produce a graphite-free, steel-like surface on SGI.